Wacana Antagonisme Fans Kpop Blackpink dalam Media Berita Online Indonesia - Saputri, Nur Amala (Jurnal Media dan Komunikasi, 2024)
ABSTRACT This research aims to determine the discourse of Blackpink fan antagonism which is built through news by Kumparan.com. Kumparan as one of Indonesia's online news channels is assumed to be contributing to the contestation of perpetuating the antagonistic image of Kpop fans in Indonesia. The researcher uses the critical paradigm and Laclau's theory of discourse analysis as a tool for analysis. The method used is hegemonic and deconstructive analysis which is used to analyze research objects. The data collection technique uses hashtags and search features on the Kumparan site or platform. The news classification used as the research corpus is those belonging to the hashtags #Blackpink, #Blink, #Persija, #Jackmania (10 news stories in March 2023). There are 2 findings, firstly, the practice of platypus journalism carried out by Kumparan actually minimizes the exploration of in-depth information and does not represent the public's voice fairly. This actually gives rise to partiality and clarifies the agenda of the Kumparan media. Then, the second finding is that Blackpink fans (Blink) antagonism discourse is constructed using negative and quite provocative words. Moreover, Kumparan also helped build subject interpellation as a discursive strategy in building an antagonistic discourse field for Blackpink by presenting formal parties and supporting parties. Keywords: Discourse; Laclau; Fans; Blackpink; Kumparan